HYDROGEOLOGICAL STUDY OF AREA BETWEEN NAJAF – KARBALAA CITIES - Ali, Batool (Iraqi Journal of Science, 2024)
The area which located along the road between the Karbalaa and Najaf cities is one ofthe important areas in terms of hydrogeological view due to containing the groundwaterreservoirs of sandy Debdebba and Dammam limestone formations. The exposed part ofthe Sandy Debdibba formation helps to renew its water and maintenance of groundwaterstorage through the infiltration of rainfall and surface floods. The groundwatermovement in this reservoir flows from west towards east and south-east direction, whilethe quality of groundwater in this reservoir is characterized to be highly concentratedwith dissolved salts which are generally ranged between (2000) to (4700) PPM. The Dammam Formation is consider as an aquifer in this area where its westernhydraulic boundary characterized to be continuous underground water movementcoming from west and south -west direction of the Western Desert. Most of formationthickness considered being saturated thickness of reservoir due to containing wide andexpanded caves and cracks as a result of structural and weathering impact. These factorshelped to expand cracks on formation exposed surface as well as caves inside it. TheGroundwater movement in this aquifer flows from west towards Euphrates River. Thesalinity of groundwater in this reservoir is varied ranging between (1900) to (3700) PPMwith calcium sulfate type.